Sedentarism and Metabolic Syndrome: Broadening the measurement of sedentarism - Magalhães, Lucélia Cunha; DO, Silva; MJ, Araújo; I, RN Lessa; N, Almeida Filho; EML, Aquino (Archives of Community Medicine and Public Health, 2019)
The metabolic syndrome (MS) is a combination of cardiovascular risk factors, including visceral obesity, low HDL cholesterol level, increased triglycerides, hyperglycemia and high blood pressure. This sequence of risk factors contributes towards the development of atherosclerotic cardiovascular disease (ACVD) and diabetes mellitus. Sedentarism is not widely studied. This habit is a determinant factor for chronic or acute diseases. This study tests the hypothesis of the association between overall sedentarism, including professional work, travel and leisure and the MS, in adult men and women in Salvador, Bahia. A population based cross-sectional study of both genders, ages ≥ 20 years. MS is defined by the criteria of the International Diabetes Foundation, characterized as the MS when considering the presence of abdominal obesity (waist ≥84 cm for women and ≥ 88cm for men) plus two of the following criteria: arterial hypertension (≥130/85mmHg) hyperglycemia (≥100mg/dl) hypertriglyceridemia (≥150mg/dl). Hypoalphalipoproteinemia (hdl-cholesterol below 40mg/dl for women and below 50 for men). Sedentarism is defined by means of the four criteria of physical inactivity described below. Athletes were excluded. Inactivity in the professional work: lack of physical activity in the professional work or the presence of light physical activity such as: working mostly seated or less than 25% of the time standing or moving around. Inactivity in household work: lack of household work or light work, such as small repairs, light cleaning or preparation of food. Physical inactivity during travel to work: traveling by car or bus, walking less than 30 minutes as well as performing most of the outside activities by car or walking. Physical inactivity during leisure: leisure does not include physical activities. The final sample totaled 1,333 individuals. In logistic regression, the adjusted prevalence ratio (PR) of overall sedentarism and the MS for women was of 1.31 (CI95% 0.86-1.91). For men the adjusted prevalence ratio was of 1.68 (CI95% 1.05-2.53), statistically significant. This paper reveals, in men, that overall sedentarism is associated to the MS. There was no statistically significant association between sedentarism exclusively in leisure and the MS. Marital status was a confounding factor and raises the issue of this variable not being widely studied as a cardiovascular risk factor.